IJCNN-91-Seattle International Joint Conference on Neural Networks
DOI: 10.1109/ijcnn.1991.155371
|View full text |Cite
|
Sign up to set email alerts
|

On fuzzy neuron models

Abstract: In recent years, an increasing number of researchers have become involved in the subject of fuzzy neural networks in the hope of combining the strengths of fuzzy logic and neural networks and achieving a more powerful tool for fuzzy information processing and for exploring the functioning of human brains. In this paper, an attempt has been made to establish some basic models for fuzzy neurons. First, several possible fuzzy neuron models are proposed. Second, some learning (training) and adaptation mechanisms f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…However, only numerical or crisp data is suitable for the aforementioned fuzzy neural networks (FNNs) and the knowledge of experts is always of linguistic type. Thus, Gupta and Qi [31] presented some models with fuzzy neurons but no learning algorithms within. Thereafter, a number of publications were cited in a survey paper [32], the authors discussed the learning algorithms and applications for FNNs with fuzzy inputs, weights and outputs [33].…”
Section: Fuzzy Neural Network (Fnns)mentioning
confidence: 99%
“…However, only numerical or crisp data is suitable for the aforementioned fuzzy neural networks (FNNs) and the knowledge of experts is always of linguistic type. Thus, Gupta and Qi [31] presented some models with fuzzy neurons but no learning algorithms within. Thereafter, a number of publications were cited in a survey paper [32], the authors discussed the learning algorithms and applications for FNNs with fuzzy inputs, weights and outputs [33].…”
Section: Fuzzy Neural Network (Fnns)mentioning
confidence: 99%
“…Gupta and Qi [1] introduced basics models for fuzzy neurons. They did not show any calculation or perform any experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Klir Since, for any of these operations, [A⊗B] α is a closed interval for each α∈(0, 1] and A, B are fuzzy numbers, A ⊗ B is also a fuzzy number. For the collection of linguistic vectors (or type 2 fuzzy set) where each component is non-interactive, Mares [26] has shown that with 0 (the vector of singleton fuzzy number 0), 1 (vector of singleton fuzzy number 1), and componentwise addition and scalar multiplication, this forms a vector space. Also, with appropriate definitions of distance, these spaces exhibit the properties of metric spaces [21,27].…”
Section: Introductionmentioning
confidence: 99%
“…Pacr(l,3) and Pacr (3,2) represent the antecedent parts of those rules (define input variables as IN1 and IN2) and pcr(l,3) and pcr(3,2) the respective consequents. Take pcr( 1,3) and pcr(3,2) as 0.1 and 0.9 and defined respectively as "low" and "high"( variable OUT).…”
Section: Il=l I2=lmentioning
confidence: 99%
“…fuzzy parameters instead of crisp weights) takes place with the objective of achieving the traditional properties of flexibility and robustness in the neural network, [3], [4], [8], [lo]. Other architectures where both neural nets and fuzzy systems cooperate, more or less independently, have also been proposed in a hybrid way, [2], [l].…”
Section: Introductionmentioning
confidence: 99%